2008
DOI: 10.1097/mlr.0b013e318187d8db
|View full text |Cite
|
Sign up to set email alerts
|

Switching Health Insurance and Its Effects on Access to Physician Services

Abstract: Children and adults had disruptions in their basic access to health care when they experienced discontinuous insurance. These findings highlight the advantages of retention of enrollees as one means of promoting access to health care, in the short term, and the benefit of a continuous national health insurance program in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Interruptions in Medicaid coverage are associated with lower rates of primary and preventive care use, 1315 and persons who defer preventive care may ultimately use more acute care services, which can lead to greater downstream health care costs. For example, one study, which focused on Medicaid coverage interruptions among children in California, estimated that the rate of pediatric hospitalizations for ambulatory care sensitive conditions declined by 26% after the state provided qualifying children with 12 months of continuous Medicaid eligibility.…”
mentioning
confidence: 99%
“…Interruptions in Medicaid coverage are associated with lower rates of primary and preventive care use, 1315 and persons who defer preventive care may ultimately use more acute care services, which can lead to greater downstream health care costs. For example, one study, which focused on Medicaid coverage interruptions among children in California, estimated that the rate of pediatric hospitalizations for ambulatory care sensitive conditions declined by 26% after the state provided qualifying children with 12 months of continuous Medicaid eligibility.…”
mentioning
confidence: 99%
“…5 Other large studies have found similar results. More than 14% of California's population had discontinuity in insurance status during 2003, 6 and federal employees switch health plans at a rate of 12% per year. 7…”
Section: Incidence: How Common Is This Problem?mentioning
confidence: 99%
“…Because providers are not consistently included in all insurance networks, such switching could compel patients to change physicians to avoid significant out-of-pocket expenses, which could interrupt clinical relationships and create additional costs in time and effort for both patients and physicians. 9 Prior evidence shows that individuals switching insurance carriers are more likely to have changes in their usual source of care, 6,10,11 a problem that may be exacerbated as narrow networks become more common. 12 Since prior research has focused on the transition from no insurance to insurance coverage, 2,13 there is little evidence addressing changes in health care utilization for people who switch health insurance carriers when there are no disruptions in coverage.…”
Section: Introductionmentioning
confidence: 99%